Gender Differences in the Relationship Between Body Mass Index (Bmi) Changes and the Prevalence and Severity of Wheezing and Asthma in the First Year of Life - Mallol-Villablanca, E (Elsevier Doyma, 2015)
Background: Rapid weight gain has been recently associated with asthma at school age, but its influence in respiratory symptoms during infancy is still unknown. Methods: Answers from 6541 parents living in six different cities of Brazil to the International Study of Wheezing in Infants (EISL) questionnaire were analysed. Data from reported weight and height at birth and at one year were used to calculate BMI. Rapid body mass index (BMI) gain was defined by the difference in BMI superior to 1.0z and excessive by the difference superior to 2.0z. Results: Rapid BMI gain was found in 45.8% infants and excessive in 24.4%. Boys showed a significantly higher BMI gain than girls. Girls with rapid BMI gain showed a significantly higher prevalence of hospitalisation for wheezing (8.8% vs. 6.4%; aOR: 1.4, 95%CI: 1.1-1.8), severe wheezing (18.1% vs. 15.0%; aOR: 1.3, 95%CI: 1.0-1.5) and medical diagnosis of asthma (7.5% vs. 5.7%; aOR: 1.3, 95%CI: 1.0-1.7). Girls with excessive BMI gain also had a significantly higher prevalence of hospitalisation for wheezing (9.8% vs. 6.7%; aOR: 1.5, 95%CI: 1.1-2.0) and severe wheezing (18.9% vs. 15.5%; aOR: 1.3, 95%CI: 1.0-1.6). No significant association was found among boys. Conclusions: The majority of the evaluated infants showed BMI gain above expected in the first year of life. Although more commonly found in boys, rapid and excessive BMI gain in the first year of life was significantly related to more severe patterns of wheezing in infancy among girls. © 2014 SEICAP.